Design of Student Worksheets based on Learning Cycle 5E Learning Model for VIII Junior High School Students in Indonesia - Nur’Afifah, Rima; man, Supar (International Journal of Engineering and Technology, 2018)
The ability of a mathematical connection is one of the skills that must be possessed by students in the learning process of mathematics. Connecting mathematical concepts to gain a meaningful learning. Learning cycle 5E is one of the learning models that could improve students' mathematical connection ability. Student worksheet is a teaching material which is in the form of papers containing a summary of the materials, a guide for independent studying that refers to the basic competencies needed to be achieved. This article aims to develop a student worksheet design that provides an opportunity for students to optimize students' mathematical connection ability in the independent learning process based on the 5E learning cycle model. This research is for the development of the ADDIE model which consists of four stages, which are: analysis, design, development, implementation, and evaluation. This research is only up to the design stage. The subjects of the study are the students of SMP IT-Abu Bakar and MTs Mu'allimat Muhammadiyah Yogyakarta Indonesia. The instruments of the data collecting included interview sheets, document sheets, and description sheets. Interview sheets for retrieving curriculum data and student characteristics, document sheets for evaluating teaching materials, and description sheets for determining students' mathematical connection ability. Data analysis techniques uses qualitative data analysis. This research resulted in the design of student worksheets that fit the characteristics of students, curriculum, and teaching materials as well as packaging it based on the LC 5E model to provide a meaningful learning experience. Student worksheets are designed to facilitate students in learning activities and provide opportunities for students to optimize mathematical connection capabilities that are integrated into the learning model LC 5E.